Dr. Hal J. Todd and Dr. Ron J. Mcbeath. - Unknown:::Creator::::::::::::
Written on verso: "Theatre Arts Department Chairman Dr. Hal J. Todd and Dr. Ron J. McBeath, director of the Instructional Resources Center, pose amid memorabilia of late Hollywood movie mogul Jesse Lasky. Items were donated to SJSU Lasky's daughter, Betty Lasky. The pioneer film producer was reared in San Jose."